The changing relationship between earnings expectations and earnings for value and growth stocks during Reg FD - de Jong, Pieter J.; Apilado, Vince P. (Journal of Banking & Finance, 2009)
Regulation Fair Disclosure (Reg FD) altered the voluntary disclosure practices of firms with publicly traded securities, thereby affecting relationships between value and growth stock expectations and actual earnings. The results show that earnings forecasts for both stock groups are biased but that bias is less after the introduction of Reg FD. In fact, the difference in pre/post FD forecast bias is larger for growth stocks, suggesting that before Reg FD, analysts did not just misinterpret news but consciously tried to maintain relationships with growth firm managers. However, Reg FD limited these relationships severing the monetary advantage that might be gained from manipulating forecasts.